Non-occupational exposure to asbestos and malignant mesothelioma in the Italian National Registry of Mesotheliomas. Issue 11 (19th October 2010) - Mirabelli, Dario; Cavone, Domenica; Merler, Enzo; Gennaro, Valerio; Romanelli, Antonio; Mensi, Carolina; Chellini, Elisabetta; Nicita, Carmela; Marinaccio, Alessandro; Magnani, Corrado; Musti, Marina
Abstract : Background: Malignant mesotheliomas are strictly related to asbestos, but in a proportion of cases no exposure can be recalled. Published estimates of this proportion have important variations. Historical and geographical differences in the fraction of cancer due to any given exposure are to be expected, but incomplete identification of non-occupational exposures may have played a role. Methods: To assess the role of non-occupational exposures in causing malignant mesotheliomas in Italy, the exposures of cases registered by the national mesothelioma registry (ReNaM) were examined. ReNaM started in 1993 in five regions and currently covers 98% of the Italian population. Information on occupational and non-occupational exposures of cases is collected whenever possible. Results: From 1993 to 2001 ReNaM registered 5173 malignant mesothelioma cases, and exposures were assessed in 3552 of them. 144 and 150 cases with exposures limited to environmental (living in the neighbourhood of an industrial or natural source of asbestos) or familial (living with a person occupationally exposed to asbestos) circumstances, respectively, were identified, accounting for 8.3% of all cases. Conclusions: Geographical variations in the proportion of cases due to non-occupational exposures may be explained by the past distribution of asbestos-using industries.